Modification method of waste concrete recycled fine aggregate

By surface etching of waste concrete recycled fine aggregate and processing of in-situ grown nanomaterials, the problems of high water absorption rate of recycled fine aggregate and poor fluidity of recycled mortar are solved, and the mechanical properties and flow properties of recycled mortar are significantly improved.

CN119912186APending Publication Date: 2025-05-02SOUTHEAST UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510098806.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art cannot effectively reduce the water absorption rate of waste concrete recycled fine aggregates and improve their application performance in concrete, especially the problem of poor fluidity of the prepared recycled mortar.

Method used

The regenerated fine aggregates were surface etched by surface etching using a composite acid solution of hydrofluoric acid and hydrochloric acid, and CO2 gas was introduced into the precursor solution, so that the regenerated fine aggregates of nanosilicon dioxide and amorphous aluminum hydroxide were achieved in situ.

Benefits of technology

It effectively reduces the water absorption rate of regenerated fine aggregates, improves the early strength and fluidity of regenerated mortars, improves the interface transition zone between aggregates and cement, and forms a dense connection structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912186A_ABST
    Figure CN119912186A_ABST
Patent Text Reader

Abstract

The invention discloses a modification method of waste concrete recycled fine aggregate, which comprises the following steps: (1) carrying out surface etching on the recycled fine aggregate by using a composite acid solution of hydrofluoric acid and hydrochloric acid, and repeatedly washing after etching until eluate is neutral; and (2) adding the regenerated fine aggregate into the precursor solution, continuously introducing CO2 gas into the solution, stopping introducing the CO2 gas when a corresponding pH value is reached, carrying out solid-liquid separation after full reaction, and drying the separated solid particles to obtain the regenerated fine aggregate on which the nano material grows in situ. The method provided by the invention solves the problems of high water absorption rate of the existing recycled fine aggregate and poor flowability of the prepared recycled mortar, and by in-situ growth of the nano material on the surface of the recycled fine aggregate, the mechanical properties and flowability of the recycled mortar are effectively improved while the dispersibility of the nano material in a cement material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for modifying waste concrete recycled fine aggregate. Background Art

[0002] With the development of urban construction, the acceleration of urbanization, the demolition and reconstruction of a large number of old buildings, the renovation of cement concrete pavements, and the damage caused to existing buildings by natural disasters such as floods and earthquakes, more and more waste concrete is generated. Fine aggregate is an indispensable building material in concrete and is in huge demand. In order to alleviate this problem, the industry decided to crush the waste concrete into sand and gravel to replace natural aggregate and reuse it in concrete. However, since the surface of the recycled fine aggregate is covered with old cement stone, it has high water absorption and porosity, and damage accumulates during the crushing process, resulting in a large gap in the physical properties of the recycled fine aggregate compared to the natural fine aggregate.

[0003] The performance of recycled fine aggregate is improved by modifying recycled aggregate with nanomaterials. At present, when nanomaterials are used to modify recycled concrete fine aggregate, the recycled fine aggregate is generally pre-soaked or pre-coated with a nano-water solution. However, since nanomaterials are easy to agglomerate in aqueous solutions and wrap a part of the water, the water absorption rate of the treated recycled aggregate increases. In addition, ordinary nano-silicon oxide or aluminum oxide has little effect on improving the water absorption rate of recycled aggregate, and the recycled mortar prepared with recycled aggregate treated with commercial nanoparticles will greatly reduce the fluidity.

[0004] In addition, since recycled fine aggregate contains a large amount of quartz minerals, its surface properties are stable, smooth, acid and alkali resistant, and foreign particles are difficult to adsorb on its surface. Therefore, the existing in-situ growth process of nanomaterials cannot be directly applied to recycled fine aggregate.

[0005] In summary, the existing technology currently has the problem that the water absorption rate of recycled fine aggregate cannot be effectively reduced by using commercial nanomaterials for modification and the prepared recycled mortar products have poor fluidity, and the existing in-situ growth technology cannot be used for surface treatment of recycled fine aggregate. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a method for modifying waste concrete recycled fine aggregate. The recycled fine aggregate with in-situ growth of nanomaterials obtained by the method, on the one hand, utilizes the small size effect of nanomaterials to fill the pores of the recycled fine aggregate, thereby effectively solving the problem of high water absorption of the recycled fine aggregate; on the other hand, the nanomaterials on the recycled fine aggregate can react with cement to produce more hydration products, thereby compacting the interface transition zone between the recycled aggregate and the fresh cement, thereby significantly improving the early strength of the recycled mortar.

[0007] Technical solution: The modification method of waste concrete recycled fine aggregate of the present invention comprises the following steps:

[0008] (1) Using a composite acid solution of hydrofluoric acid and hydrochloric acid to etch the surface of the recycled fine aggregate, and then repeatedly rinsing with deionized water until the washing liquid is neutral;

[0009] (2) Adding recycled fine aggregate to a precursor solution, and then continuously introducing CO2 gas into the solution. When the corresponding pH value is reached, the introduction of CO2 gas is stopped. After sufficient reaction, the solid and liquid are separated. The separated solid particles are dried to obtain recycled fine aggregate with in-situ growth of nanomaterials.

[0010] Wherein, in step (1), in the composite acidic solution, the mass concentration of hydrofluoric acid is 1-2%, and the mass concentration of hydrochloric acid is 5-10%.

[0011] Wherein, in step (1), the etching temperature of the recycled fine aggregate in the composite acidic solution is 20 to 40° C., and the etching time is 10 to 30 minutes.

[0012] Wherein, in step (2), the precursor solution is a sodium metasilicate solution or a sodium metaaluminate solution, and the concentration of the precursor solution is 0.10 to 0.25 mol / L.

[0013] The mass volume ratio of the recycled fine aggregate to the sodium silicate solution or the sodium aluminate solution is 25-750 g: 100-3000 mL.

[0014] Wherein, in step (2), the volume concentration of the introduced CO2 gas is not less than 99%, and the gas flow rate is 0.1 to 0.4 L / min.

[0015] Wherein, in step (2), the reaction temperature of the system is 20 to 60°C when CO2 gas is introduced.

[0016] Wherein, in step (2), when the pH value of the precursor solution drops to 8, the introduction of CO2 gas is stopped.

[0017] Wherein, in step (2), the stirring speed is 250-600 r / min; after stopping the introduction of CO2 gas, stirring is continued for 2-4 h.

[0018] Wherein, in step (2), after the reaction is completed, the solid and liquid phases are separated by filtration, the modified recycled fine aggregate is rinsed three times with deionized water, the liquid is centrifuged and washed three times with deionized water, and then vacuum filtered to obtain a filter cake, and the solid and the filter cake are dried at 50-110° C. for 24-72 hours.

[0019] Wherein, in step (2), the nanomaterials grown in situ on the surface of the recycled fine aggregate are nano silicon dioxide and amorphous aluminum hydroxide.

[0020] The mass of the in-situ grown nano silicon dioxide is 0.87% to 1.33% of the mass of the recycled fine aggregate; the mass of the in-situ grown nano aluminum hydroxide is 0.14% to 0.15% of the mass of the recycled fine aggregate.

[0021] The regenerated fine aggregate with nanomaterials grown in situ prepared by the present invention is mixed with cement and water in a mass ratio of 5:2:1, and stirred evenly to obtain regenerated mortar; wherein the cement used is P·O52.5 or standard cement. In the process of preparing mortar, the regenerated fine aggregate with nanomaterials grown in situ prepared by the present invention can replace natural aggregate 100%.

[0022] The method of the present invention etches the surface of the recycled fine aggregate, releases active sites on the surface of the recycled fine aggregate for nanoparticle adsorption, provides an adsorption driving force for in-situ growth of nanomaterials, and obtains a recycled fine aggregate with surface-loaded active nanomaterials. The nanoparticles are adsorbed on the active sites of the recycled fine aggregate, which can reduce the proportion of self-agglomeration and flocculation of the nanomaterials, and can effectively reduce the water demand of the recycled mortar or recycled concrete, and improve the fluidity of the slurry; on the other hand, it can strengthen the interface transition zone between the fresh cement and the recycled fine aggregate, and improve the mechanical properties of the recycled mortar. The present invention can improve the problems of high water absorption in the recycled fine aggregate and poor fluidity of the prepared recycled mortar, and improve the dispersibility of the nanomaterials in the cement material by in-situ growth of the nanomaterials on the surface of the recycled fine aggregate, while improving the mechanical properties and fluidity of the recycled mortar.

[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: the nano-silicon dioxide grown in situ on the surface of the recycled fine aggregate prepared by the method of the present invention can not only promote cement hydration and produce more hydrated calcium silicate, but the nano-aluminum hydroxide grown in situ can generate hydrated calcium aluminosilicate and calcium sulfonate, and these additional hydration products are concentrated in the interface transition zone between the fresh cement and the recycled fine aggregate, forming a dense connection structure between the aggregate and the cement, thereby improving the weak link of the interface in the recycled mortar and improving the mechanical properties of the recycled mortar; on the other hand, the nano-materials generated on the surface of the recycled fine aggregate will be fully dispersed with the recycled fine aggregate, avoiding the problem of agglomeration between the nano-materials, thereby improving the mechanical properties of the recycled mortar while also improving its flow properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the microscopic morphology of the original recycled fine aggregate;

[0025] Figure 2 This is the microscopic morphology of the recycled fine aggregate after in-situ growth of nano-SiO2 in Example 1;

[0026] Figure 3The particle size statistics of in-situ grown nano-silicon dioxide in Examples 1, 2, and 3 are shown. DETAILED DESCRIPTION

[0027] The recycled fine aggregate used in the present invention is crushed from demolished concrete, and the particle size is less than 4.75 mm.

[0028] Example 1

[0029] The method for modifying waste concrete recycled fine aggregate of the present invention comprises the following steps:

[0030] (1) preparing 20 mL of a composite acid solution, wherein the mass fraction of hydrofluoric acid is 1% and the mass fraction of hydrochloric acid is 5%; soaking the recycled fine aggregate in the composite acid solution, heating the recycled fine aggregate in a water bath to 20° C., and soaking the recycled fine aggregate for 10 minutes; taking the recycled fine aggregate out after soaking, and repeatedly rinsing the recycled fine aggregate with deionized water until the pH of the eluate is 7;

[0031] (2) preparing 100 mL of a sodium metasilicate solution having a molar concentration of 0.1 mol / L, adding 25 g of the recycled fine aggregate treated in step (1), mechanically stirring at a rate of 250 r / min for about 5 min, monitoring the pH value of the reaction system in real time using a pH meter, and adding dropwise 0.1 mol / L of sodium hydroxide solution to adjust the initial pH value of the reaction system to 12;

[0032] (3) The above solution was transferred to a water bath thermostat, CO2 was introduced into the reaction system at a ventilation rate of 0.1 L / min, the reaction temperature was controlled at 20°C, and stirring was continued at a rate of 250 r / min; when the pH of the reaction system dropped to 8, the CO2 was stopped and stirring was continued at a speed of 250 r / min for 2 h; the product obtained by the reaction was separated into solid and liquid, the solid was rinsed with deionized water for 3 times, the liquid was centrifuged and washed with deionized water for 3 times, and then vacuum filtered to obtain a filter cake, and the solid and the filter cake were placed in a 50°C forced air drying oven and dried for 72 h. This process produced recycled fine aggregate particles with nano-SiO2 grown on the surface in situ.

[0033] In Example 1, the recycled fine aggregate particles are in-situ grown with nano-SiO2, and the mass of the in-situ grown nano-SiO2 is 0.87% of the mass of the recycled fine aggregate.

[0034] 1350 g of the recycled fine aggregate with in-situ grown nano-SiO2 in Example 1, 540 g of the standard cement and 270 g of water were mixed, stirred for 240 seconds in a planetary mixer according to the method specified in GB / T 14684, and then molded and cured to obtain recycled mortar.

[0035] Figure 1 and Figure 2 The SEM images of the microstructure of the recycled fine aggregate before and after in-situ growth of nano-SiO2 are shown in Figure 1. Figure 1 This is the surface microstructure of the recycled fine aggregate before in-situ growth of nano-SiO2. Figure 2 The surface microstructure of the recycled fine aggregate after in-situ growth of nano-SiO2. Figure 2 It can be observed that more monodispersed spherical particles appear on the surface of the originally smooth recycled fine aggregate, and there are basically no agglomerated nano-SiO2 clusters.

[0036] Figure 3 ImageJ was used to count the particle size and particle size distribution of nano-SiO2 grown in situ in the SEM image.

[0037] Example 2

[0038] The method for modifying waste concrete recycled fine aggregate of the present invention comprises the following steps:

[0039] (1) preparing 200 mL of a composite acid solution, wherein the mass fraction of hydrofluoric acid is 1% and the mass fraction of hydrochloric acid is 5%; soaking the recycled fine aggregate in the composite acid solution, heating the recycled fine aggregate in a water bath to 30° C., and soaking the recycled fine aggregate for 15 minutes; taking the recycled fine aggregate out after soaking, and repeatedly rinsing the recycled fine aggregate with deionized water until the pH of the eluate is 7;

[0040] (2) preparing 1000 mL of a sodium metasilicate solution having a molar concentration of 0.15 mol / L, adding 250 g of the recycled fine aggregate treated in step (1), mechanically stirring at a rate of 250 r / min for about 5 min, monitoring the pH value of the reaction system in real time using a pH meter, and adding dropwise 0.1 mol / L of sodium hydroxide solution to adjust the initial pH value of the reaction system to 12;

[0041] (3) The above solution was transferred to a water bath thermostat, CO2 was introduced into the reaction system at a ventilation rate of 0.3 L / min, the reaction temperature was controlled to be 40°C, and stirring was continued at a rate of 250 r / min; when the pH of the reaction system dropped to 8, the CO2 was stopped and stirring was continued at a speed of 250 r / min for 3 h; the product obtained by the reaction was separated into solid and liquid, the solid was rinsed with deionized water for 3 times, the liquid was centrifuged and washed with deionized water for 3 times, and then vacuum filtered to obtain a filter cake, and the solid and the filter cake were placed in an 80°C forced air drying oven and dried for 48 h. This process produced recycled fine aggregate particles with nano-SiO2 grown on the surface in situ.

[0042] In Example 2, the recycled fine aggregate particles are in-situ grown with nano-SiO2, and the mass of the in-situ grown nano-SiO2 is 1.06% of the mass of the recycled fine aggregate.

[0043] 1350 g of the recycled fine aggregate with in-situ grown nano-SiO2 in Example 2, 540 g of the standard cement and 270 g of water were mixed, stirred for 240 seconds in a planetary mixer according to the method specified in GB / T 14684, and then molded and cured to obtain recycled mortar.

[0044] Example 3

[0045] The method for modifying waste concrete recycled fine aggregate of the present invention comprises the following steps:

[0046] (1) preparing 1200 mL of a composite acid solution, wherein the mass fraction of hydrofluoric acid is 1% and the mass fraction of hydrochloric acid is 5%; soaking the recycled fine aggregate in the composite acid solution, heating the recycled fine aggregate in a water bath to 40° C., and soaking the recycled fine aggregate for 30 minutes; taking the recycled fine aggregate out after soaking, and repeatedly rinsing the recycled fine aggregate with deionized water until the pH of the eluate is 7;

[0047] (2) preparing 3000 mL of a sodium metasilicate solution with a molar concentration of 0.25 mol / L, adding 750 g of the recycled fine aggregate treated in step (1), mechanically stirring at a rate of 250 r / min for about 5 min, monitoring the pH value of the reaction system in real time with a pH meter, and adding dropwise 0.1 mol / L of sodium hydroxide solution to adjust the initial pH value of the reaction system to 12;

[0048] (3) The above solution was transferred to a water bath thermostat, CO2 was introduced into the reaction system at a ventilation rate of 0.4 L / min, the reaction temperature was controlled to 60°C, and stirring was continued at a rate of 250 r / min; when the pH of the reaction system dropped to 8, the CO2 was stopped and stirring was continued at a speed of 250 r / min for 4 h; the product obtained by the reaction was separated into solid and liquid, the solid was rinsed with deionized water for 3 times, the liquid was centrifuged and washed with deionized water for 3 times, and then vacuum filtered to obtain a filter cake, and the solid and the filter cake were placed in a 110°C forced air drying oven and dried for 24 h. This process produced recycled fine aggregate particles with nano-SiO2 grown on the surface in situ.

[0049] In Example 3, the recycled fine aggregate particles are in-situ grown with nano-SiO2, and the mass of the in-situ grown nano-SiO2 is 1.33% of the mass of the recycled fine aggregate.

[0050] 1350 g of the recycled fine aggregate with in-situ grown nano-SiO2 in Example 3, 540 g of the standard cement and 270 g of water were mixed, stirred for 240 seconds in a planetary mixer according to the method specified in GB / T 14684, and then molded and cured to obtain recycled mortar.

[0051] Comparative Example 1

[0052] Prepare 897mL of 2% nano-SiO2 suspension, and ultrasonically treat the nano-suspension for 30 minutes; spread 1350g of recycled fine aggregate on a tray, pour the nano-SiO2 suspension into the recycled fine aggregate so that it can completely immerse the recycled fine aggregate, soak for 24 hours, and then place it in a 50°C forced air drying oven for 72 hours to obtain the recycled fine aggregate soaked in the nano-SiO2 suspension.

[0053] 1350g of recycled fine aggregate soaked in the nano-SiO2 suspension in Comparative Example 1, 540g of standard cement and 270g of water were mixed, stirred for 240s in a planetary mixer according to the method specified in GB / T 14684, and then molded and cured to obtain recycled mortar.

[0054] Comparative Example 2

[0055] Prepare 57.9mL of nano-SiO2 suspension with a mass concentration of 31%, and ultrasonically treat the nano-suspension for 30 minutes; place the recycled fine aggregate in a ball-forming machine, and rotate the ball-forming machine at 60r / min to allow the recycled fine aggregate to tumble naturally. Spray the nano-SiO2 suspension on the surface of 1350g of recycled fine aggregate with a handheld spray bottle. After spraying, take out the recycled fine aggregate and place it in a 50℃ forced air drying oven for 72 hours to obtain the recycled fine aggregate coated with the nano-SiO2 suspension.

[0056] 1350g of recycled fine aggregate treated with the nano-SiO2 suspension in Comparative Example 2, 540g of standard cement and 270g of water were mixed, stirred for 240s in a planetary mixer according to the method specified in GB / T 14684, and then molded and cured to obtain recycled mortar.

[0057] Comparative Example 3

[0058] Prepare 897mL of nano-SiO2 suspension with a mass concentration of 2%, and do not disperse the nano-SiO2 suspension; spread 1350g of recycled fine aggregate on a tray, pour the nano-SiO2 suspension into the recycled fine aggregate so that it can completely immerse the recycled fine aggregate, soak for 24 hours, place it in a 50°C forced air drying oven and dry it for 72 hours to obtain the recycled fine aggregate soaked in the nano-SiO2 suspension.

[0059] 1350g of recycled fine aggregate soaked in the nano-SiO2 suspension in Comparative Example 3, 540g of standard cement and 270g of water were mixed, stirred for 240s in a planetary mixer according to the method specified in GB / T 14684, and then molded and cured to obtain recycled mortar.

[0060] Comparative Example 4

[0061] (1) Soak the recycled fine aggregate in 1200 mL of deionized water, heat the water bath to 40 °C, and soak for 30 min;

[0062] (2) preparing 3000 mL of a sodium metasilicate solution with a molar concentration of 0.25 mol / L, adding 750 g of the recycled fine aggregate treated in step (1), mechanically stirring at a rate of 250 r / min for about 5 min, monitoring the pH value of the reaction system in real time with a pH meter, and adding dropwise 0.1 mol / L of sodium hydroxide solution to adjust the initial pH value of the reaction system to 12;

[0063] (3) The above solution was transferred to a water bath thermostat, CO2 was introduced into the reaction system at a ventilation rate of 0.4 L / min, the reaction temperature was controlled to 60°C, and stirring was continued at a rate of 250 r / min; when the pH of the reaction system dropped to 8, the CO2 was stopped and stirring was continued at a speed of 250 r / min for 4 h; the product obtained by the reaction was separated into solid and liquid, the solid was rinsed with deionized water for 3 times, the liquid was centrifuged and washed with deionized water for 3 times, and then vacuum filtered to obtain a filter cake, and the solid and the filter cake were placed in a 110°C forced air drying oven and dried for 24 h. This process produced recycled fine aggregate particles with nano-SiO2 grown on the surface in situ.

[0064] In Comparative Example 4, the recycled fine aggregate particles have nano-SiO2 grown in situ, and the mass of the in-situ grown nano-SiO2 is 0.04% of the mass of the recycled fine aggregate;

[0065] 1350g of the recycled fine aggregate with in-situ grown nano-SiO2 in Comparative Example 4, 540g of the standard cement and 270g of water were mixed, stirred for 240s in a planetary mixer according to the method specified in GB / T 14684, and then molded and cured to obtain recycled mortar.

[0066] Table 1 shows the physical properties of recycled fine aggregate obtained by different nano-SiO2 treatment methods in Examples 1 to 3 and Comparative Examples 1 to 4

[0067]

[0068]

[0069] According to the analysis in Table 1, the crushing values ​​of Examples 1, 2, and 3 are all improved to varying degrees compared to the original recycled fine aggregate. At the same time, the water demand ratio of the recycled mortar of Examples 1, 2, and 3 is very close to that of the original recycled fine aggregate, indicating that the nano-SiO2 synthesized by the in-situ growth method is evenly distributed on the recycled fine aggregate, and there are fewer nano-agglomerates compared to the comparative example, and the dispersion of nano-SiO2 on the recycled fine aggregate is better. Figure 3Analysis shows that the average particle sizes of nano-SiO2 in Examples 1, 2, and 3 are 40 nm, 50 nm, and 60 nm, respectively. By controlling different reaction conditions, nano-SiO2 with controllable particle sizes can be grown in situ on the surface of recycled fine aggregate.

[0070] Table 2 shows the properties of the recycled mortar prepared from the recycled fine aggregates obtained in Examples 1 to 3 and Comparative Examples 1 to 4.

[0071]

[0072] According to the analysis of Table 2, under the same water-cement ratio, the fluidity and 3d strength of the regenerated mortar of Examples 1, 2, and 3 are stronger than those of Comparative Examples 1, 2, 3, and 4. From this analysis, it can be seen that the nano-SiO2 generated by in-situ growth adopted by the present invention has a higher degree of dispersion than the nano-suspension immersion method and the coating method. Although Comparative Examples 1 and 2 can improve the mechanical properties of the regenerated mortar, the problem of poor fluidity caused by the agglomeration of nanomaterials has not been solved. The fluidity and mechanical properties of Comparative Example 3, which does not adopt the nanomaterial dispersion method, are lower than those of the original regenerated fine aggregate. This is because the nanomaterial will form a large number of agglomerates without dispersion treatment, and will wrap a large amount of free water during the mortar mixing process, resulting in a sharp drop in fluidity; the water wrapped in the agglomerates will evaporate after a certain period of time, and finally leave a large number of pores in the agglomerates, resulting in the deterioration of the mechanical properties of the regenerated mortar. The recycled fine aggregate of Comparative Example 4 was not treated with composite acid before the in-situ growth of nanomaterials, and the in-situ grown nanoparticles could not be adsorbed on the surface of the recycled fine aggregate, resulting in the recycled fine aggregate of Comparative Example 4 still retaining the defects of the original recycled fine aggregate, and the mechanical properties of the recycled mortar prepared by the recycled fine aggregate were not improved. Therefore, the nano-SiO2 obtained by the in-situ growth method adopted in Examples 1 to 3 of the present invention can solve the problem of nano-material agglomeration, and improve the flow properties while improving the mechanical properties of the regenerated mortar. This is because the in-situ grown SiO2 on the recycled fine aggregate will be tightly adsorbed on the surface of the recycled fine aggregate, reducing the formation of agglomerates; these nanoparticles will promote cement hydration to form additional hydrated calcium silicate, and these hydration products will gather in the interface transition zone between the recycled fine aggregate and the fresh cement, the weak connection structure between the dense aggregate and the cement, and these nano-SiO2 will fill the surface pores of the recycled fine aggregate, reducing the surface porosity of the aggregate. At the same time, the method of the present invention also solves the problem that the existing in-situ growth technology cannot adapt to recycled fine aggregate.

Claims

1. A method for modifying waste concrete recycled fine aggregate, characterized in that: The steps include: (1) Using a composite acid solution of hydrofluoric acid and hydrochloric acid to etch the surface of the recycled fine aggregate, and then repeatedly rinsing after etching until the washing liquid is neutral; (2) Adding recycled fine aggregate to a precursor solution, and then continuously introducing CO2 gas into the solution. When the corresponding pH value is reached, the introduction of CO2 gas is stopped. After sufficient reaction, the solid and liquid are separated. The separated solid particles are dried to obtain recycled fine aggregate with in-situ growth of nanomaterials.

2. The modification method according to claim 1, characterized in that: In step (1), in the composite acidic solution, the mass concentration of hydrofluoric acid is 1-2%, and the mass concentration of hydrochloric acid is 5-10%.

3. The modification method according to claim 1, characterized in that: In step (1), the etching temperature of the recycled fine aggregate in the composite acid solution is 20 to 40° C., and the etching time is 10 to 30 minutes.

4. The modification method according to claim 1, characterized in that: In step (2), the precursor solution is a sodium metasilicate solution or a sodium metaaluminate solution, and the concentration of the precursor solution is 0.10 to 0.25 mol / L.

5. The modification method according to claim 4, characterized in that: The mass volume ratio of the recycled fine aggregate to the precursor solution is 25-750 g: 100-3000 mL.

6. The modification method according to claim 1, characterized in that: In step (2), the volume concentration of the introduced CO2 gas is not less than 99%, and the gas flow rate is 0.1 to 0.4 L / min.

7. The modification method according to claim 1, characterized in that: In step (2), when the pH value of the precursor solution drops to 7.5-8, the introduction of CO2 gas is stopped.

8. The modification method according to claim 1, characterized in that: In step (2), the stirring speed is 250-600 r / min; after stopping the introduction of CO2 gas, stirring is continued for 2-4 h.

9. The modification method according to claim 1, characterized in that: In step (2), the nanomaterials grown in situ on the surface of the recycled fine aggregate are nano silicon dioxide and amorphous aluminum hydroxide.

10. The modification method according to claim 9, characterized in that: The mass of the in-situ grown nano silicon dioxide is 0.87% to 1.33% of the mass of the recycled fine aggregate; the mass of the in-situ grown nano aluminum hydroxide is 0.14% to 0.15% of the mass of the recycled fine aggregate.

Citation Information

Patent Citations

  • Preparation method of solid waste surface in-situ growth nano-particles

    CN107954623A

  • Method for strengthening recycled aggregate and improving bonding of recycled aggregate with mortar

    CN110759657A

  • Reinforced recycled concrete and production process thereof

    CN113105181A

  • Preparation method of modified recycled coarse aggregate and recycled concrete

    CN119080415A

  • Modified recycled aggregate high-temperature-resistant ultrahigh-ductility concrete and preparation method thereof

    CN119241180A